Dysfagia. Część 2: dysfagia u pacjentów oddziałów intensywnej terapii - Dylczyk-Sommer, Anna (Anestezjologia Intensywna Terapia, 2020)
Dysphagia is a common problem among ICU patients. The frequency of dysphagia increases with age and sometimes symptoms can be difficult to recognise. But the consequences of dysphagia can be very serious, including aspiration and subsequently aspiration pneumonia. Therefore, knowing mechanisms and symptoms causing dysphagia is very important and should be well recognised. Proper diagnosis allows one to prevent further complications. However, both the diagnosis and treatment can be very complicated, especially among the patients who do not cooperate. In many cases, the implementation of an appropriate nutrition strategy and proper rehabilitation can alleviate the symptoms of dysphagia and avoid the most severe complications.